2016
DOI: 10.1136/bmjopen-2016-013509
|View full text |Cite
|
Sign up to set email alerts
|

Associations of lipid levels during gestation with hypertensive disorders of pregnancy and gestational diabetes mellitus: a prospective longitudinal cohort study

Abstract: ObjectiveTo assess associations of elevated lipid levels during gestation with hypertensive disorders of pregnancy (HDP) and gestational diabetes mellitus (GDM).MethodsThis prospective cohort study was conducted in a tertiary maternal hospital in Shanghai, China from February to November 2014. Lipid constituents, including triglycerides (TGs), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-c) and high-density lipoprotein cholesterol (HDL-c) of 1310 eligible women were assessed in the first (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
58
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 22 publications
8
58
0
1
Order By: Relevance
“…In addition to dysregulation of glycaemia and blood pressure, maternal lipid disorders during early pregnancy, including total cholesterol, LDL‐c, non‐HDL‐c, and ApoB levels, were positively correlated with GDM. While some studies found no significant association between total and LDL cholesterol with the risk for GDM, our observations confirm the findings of other studies, which demonstrated a strong link between cholesterol levels during early gestation and GDM . ApoB is an essential component of LDL particles, and its increase during pregnancy is parallel to the increase in LDL‐c .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition to dysregulation of glycaemia and blood pressure, maternal lipid disorders during early pregnancy, including total cholesterol, LDL‐c, non‐HDL‐c, and ApoB levels, were positively correlated with GDM. While some studies found no significant association between total and LDL cholesterol with the risk for GDM, our observations confirm the findings of other studies, which demonstrated a strong link between cholesterol levels during early gestation and GDM . ApoB is an essential component of LDL particles, and its increase during pregnancy is parallel to the increase in LDL‐c .…”
Section: Discussionsupporting
confidence: 89%
“…While some studies found no significant association between total and LDL cholesterol with the risk for GDM, 27,28 our observations confirm the findings of other studies, which demonstrated a strong link between cholesterol levels during early gestation and GDM. 29,30 ApoB is an essential component of LDL particles, and its increase during pregnancy is parallel to the increase in LDL-c. 31 Our study identified a significant positive relationship between ApoB level and GDM in PCOS women. In contrast, no significant association was found between ApoB during early gestation and GDM in non-PCOS women.…”
Section: Discussionmentioning
confidence: 99%
“…In China, HDP occur in 4%-11% of pregnant women. [2][3][4] HDP have been associated with adverse health outcomes for both mothers and children, including subsequent hypertension and chronic kidney disease for mothers, 5,6 childhood overweight/obesity, type 2 diabetes and attention deficit/hyperactivity disorder (ADHD). [7][8][9] Therefore, it is important to identify the risk factors associated with HDP during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several studies suggested that lipid patterns may identify women at risk of developing GDM (Dos Santos‐Weiss, Rea, & Fadel‐Picheth, ; Enquobahrie, Williams, Qiu, & Luthy, ; Ryckman et al, ; Shen, Liu, Chen, He, & Cheng, ; Wang et al, ). In a prospective longitudinal cohort study of 1300 Chinese women, Shen et al () reported that hypertriglyceridemia during gestation was a risk factor for GDM and hypertensive disorders of pregnancy. Also in a Chinese population, another study with 934 nondiabetic women showed maternal hypertriglyceridemia in late pregnancy to be independently associated with increased risk of GDM, preeclampsia, and macrosomia (Jin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies assessing the association between early‐pregnancy lipid profiles and GDM risk are limited and inconsistent (Dos Santos‐Weiss et al, ; Enquobahrie et al, ; Shen et al, ; Wang et al, ). It is unclear whether hyperlipidemia and mainly hypertriglyceridemia occur exclusively later in pregnancy after the manifestation of GDM or whether they existed before insulin resistance.…”
Section: Introductionmentioning
confidence: 99%